HUBUNGAN ANTARA TENSION TYPE HEADACHE DENGAN GEJALA GANGGUAN DEPRESI PADA MAHASISWA FKIK UMY - Emma Juliana (Fakultas Kedokteran dan Ilmu Kesehatan UMY, 2016)
Depression is a state of disorder tone generally feeling characterized by feelings of sadness, apathy, pessimism, and loneliness. The prevalence rate of depressive disorder is increasing, including those having comorbidity with physical illnesses. One of the medical conditions that has been related to depressive disorder is tension type headache (TTH). This research aims to know relationship between tension type headache and depressive disorder symptoms. This research is an analytic survey with a cross sectional desain. The sample in this research is 45 student of Faculty Medicine Muhammadiyah Yogyakarta were willing and meet the inclusion criteria, selected with systematic random sampling. 45 subjects were divided into two different group, those who diagnosed TTH and without TTH. They were examined using Beck Depression Inventories II (BDI-II). The data was analyzed using Spearman hypothesis test. The result show that at responden without TTH have minimal symptoms of depressive disorder 64%, mild depression 27%, moderate depression 9%, and severe depression 0%. Respondent were diagnosed TTH have minimal symptoms of depressive disorder 27%, mild depression 56%, moderate depression 17%, and severe depression 0%. The most frequent depressive disorder symptoms of the respondent without TTH is minimal depression 64%. The most frequent depressive disorder symptoms of the respondent with TTH is mild depression 56%. Thus, the end result of the hypothesis test show that there are relationship between tension type headache and depressive disorder symptoms (P=0.002). In conclusions, there is a positive relationship between tension type headache and depressive disorder symptoms, in the respondent with tension type headache have higher levels of depressive symptoms than respondent without tension type headache.